EVALUASI PROGRAM FASILITATOR DESA INTENSIF DI KABUPATEN KENDAL - Malik Ibrahim (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
Intensive Village Facilitator Program as an education service to non-prosperous village that conducted by Nonformal Education. There are two intensive villages chosen in district of Kendal, There are village Sumur in Brangsong district and village Sukodadi in Singorojo district. The service goal is especially for the people who have never got education, dropped out of school, are unemployeed and other people who want to increase their knowledge and skill for provision to have a better life. The study was evaluation research, using qualitative approach with population was intensive village in Kendal Regency. That has aim to reveal the success rate of Nonformal Education Program in Intensive Village. The result shows that: if observed from the success indicator, facilitator program in Kendal Regency is successful, because seven out of eight indicator is fulfilled (87,5%), but if observed from the program purpose and society servable rate, the facilitator program not yet succeded, because from 1884 study society aspirant, only 147 study society (7,9%) can be served, because of the limited fund, facilities, labour, and due to difficult geographic location.